210k views
3 votes
Y=2x+6, 3y=x-2 solve for unknown variables

2 Answers

4 votes
X=-4
Y=-2
Step by step explanation
User Ehm
by
4.6k points
7 votes

Step: Solvey=2x+6for y:

y=2x+6

Step: Substitute2x+6foryin3y=x−2:

3y=x−2

3(2x+6)=x−2

6x+18=x−2(Simplify both sides of the equation)

6x+18+−x=x−2+−x(Add -x to both sides)

5x+18=−2

5x+18+−18=−2+−18(Add -18 to both sides)

5x=−20

5x/5=−20/5

(Divide both sides by 5)

x=−4

Step: Substitute−4forxiny=2x+6:

y=2x+6

y=(2)(−4)+6

y=−2(Simplify both sides of the equation)

Answer:

x=−4 and y=−2

I hope it helps you